Evaluating the impact of employees’ perception of identity threat on knowledge sharing behavior during COVID-19: The mediation and moderation effect of social capital and reward system - Peng, Michael Yao-Ping (Frontiers in Psychology, 2022)
Quarantine policies introduced in the context of COVID-19 are affecting business operations and slowing down the flow rate of the overall economy. Different degrees and types of threats occur in both the living environment and the working environment during the epidemic prevention, which causes many additional uncertainties. The impact on employees is the identity threat from environment and organizations. This is different from the related research on the identification and impact of the threat before the occurrence of COVID-19. However, in the post-pandemic period, companies continue to strengthen important factors that can increase innovation and recovery, including the role of employee knowledge sharing. The organizational inequity and lack of organizational justice bring about the threat of internal identification in organizations. In order to ensure their own interests in organizations, employees may think twice when sharing knowledge. Therefore, this study explores the relationship among employees’ identity threat, social capital and knowledge sharing behavior from the perspective of organizational behavior. In this study, a sample of high-tech employees was conducted, and a total of 434 questionnaires were obtained. The research results show that employees’ perception of identity threat has a negative impact on knowledge sharing behavior and positively affects social capital; employees’ social capital positively affects their knowledge sharing behaviors; and organizational reward system moderates the relationship between identity threat and knowledge sharing behavior. Based on the comprehensive research findings, this research proposes corresponding theoretical and practical implications.